PROGRAM KEGIATAN BUILD UP CARING SEBAGAI PELATIHAN KECERDASAN MULTI INTELEJENSIA BAGI MAHASISWA PROGRAM STUDI ARSITEKTUR UNIVERSITAS KRISTEN PETRA - Christine Wonoseputro (SHARE: Journal of Service Learning, 2013)
Each Petra Christian university student should join either community service or service learning course as a compulsory to complete the undergraduate program. It has influenced the learning environment especially in architecture department of Petra Christian University. The learning outcome of this program is to provoke the students to be able to think critically and to be care of the community needs, so that they can be whole beings that will become visionair leaders in the future. This kind of program was being set accordingly to Petra Christian University’s academic vision and also university excellence value.